Longitudinal Evaluation of the Structure of Replicating and Circulating Hepatitis C Virus Quasispecies in Nonprogressive Chronic Hepatitis C Patients - Cabot, Beatriz (American Society for Microbiology, 2001)
In previous cross-sectional studies, we demonstrated that, in most patients with chronic hepatitis C, the composition and complexity of the circulating hepatitis C virus (HCV) population do not coincide with those of the virus replicating in the liver. In the subgroup of patients with similar complexities in both compartments, the ratio of quasispecies complexity in the liver to that in serum (liver/serum complexity ratio) of paired samples correlated with disease stage. In the present study we investigated the dynamic behavior of viral population parameters in consecutive paired liver and serum samples, obtained 3 to 6 years apart, from four chronic hepatitis C patients with persistently normal transaminases and stable liver histology. We sequenced 359 clones of a genomic fragment encompassing the E2(p7)-NS2 junction, in two consecutive liver-serum sample pairs from the four patients and in four intermediate serum samples from one of the patients. The results show that the liver/serum complexity ratio is not stable but rather fluctuates widely over time. Hence, the liver/serum complexity ratio does not identify a particular group of patients but a particular state of the infecting quasispecies. Phylogenetic analysis and signature mutation patterns showed that virtually all circulating sequences originated from sequences present in the liver specimens. The overall behavior of the circulating viral quasispecies appears to originate from changes in the relative replication kinetics of the large mutant spectrum present in the infected liver.